A micrometeorological flux perspective on brush management in a shrub-encroached Sonoran Desert grassland - Vivoni, Enrique; Perez Ruiz, Eli Rafael; Scott, Russell; Naito, Adam; Archer, Steven; Biederman, Joel; Templeton, Nicole (2022)
Woody plant encroachment typically limits the forage productivity of managed rangelands and alters a panoply of semiarid ecosystem processes and services. Intervention strategies to reduce woody plant abundance, collectively termed “brush management”, often lack observations to quantify and interpret changes in ecosystem processes. Furthermore, comparative studies between treated and untreated areas should account for heterogeneity since plant composition, microclimate, topoedaphic factors, and historical land use can substantially vary over short distances in drylands. Here, we quantify ecosystem responses to brush management after a single aerial herbicide application on an 18 hectare shrub-encroached grassland (savanna) in southern Arizona, USA. We conducted a pre- and post-treatment comparison of a flux tower site in the treated area with that of a tower in a nearby control site. The comparison, spanning a seven year period, included: (1) ground, airborne, and satellite-based measurements of vegetation structure, and (2) eddy covariance measurements. The herbicide treatment defoliated the dominant shrub (velvet mesquite, Prosopis velutina) and led to a temporary reduction in summer greening, but full foliar recovery occurred within two years. Contrary to expectations, perennial grass cover decreased and bare soil cover increased on the treated site. Relative amounts of evapotranspiration were reduced, while carbon uptake increased during the 2 year post-treatment period at the treated site due to a higher water use efficiency in the following spring. During mesquite recovery, carbon uptake was enhanced by higher gross primary productivity and accompanied by a decrease in ecosystem respiration relative to the untreated site. Mesquite recovery was facilitated by access to deep soil water, carbohydrate reserves in rooting systems, and a lower competition from reduced perennial grass cover.